Higher Order Thinking Skills (HOTS)-Based Students’ Worksheets in Thermodynamics Materials - Nadhiroh, Nuraini; Latifah, Sri (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to produce a Higher Order Thinking Skills (HOTS)-based Student Worksheet on Thermodynamic Material and determine the feasibility of the product. The method used is Research and Development (R andD). Product validation was carried out by 2 material expert and 2 media expert. The study was conducted at SMAN 1 Sukoharjo, SMAN 1 Adiluwih, MA Ma'arif Keputran with the research subjects are students in grade XI. Data collection was carried out using a non-test instrument in the form of a questionnaire. The rating scale uses a Likert scale, 5 highest values to 1 lowest value. The results of the material expert validation were 92% with the Very Eligible criteria and the media expert was obtained 100% with the Very Eligible criteria. LKPD was tested through 2 stages, small group trials and field trials. The results obtained were 73% for small group trials, 89% for field trials. So that the HOTS-based LKPD is feasible to use with good interpretation.